A New Distortion Solution for NIRC2 on the Keck II Telescope. (24th June 2016) - Service, M.; Lu, J. R.; Campbell, R.; Sitarski, B. N.; Ghez, A. M.; Anderson, J.
Abstract: We present a new geometric distortion model for the narrow-field mode of the near-infrared camera (NIRC2) fed by the adaptive optics system on the W. M. Keck II telescope. The adaptive optics system and NIRC2 camera were realigned on 2015 April 13. Observations of the crowded globular cluster, M53, were obtained before and after the realignment to characterize the geometric field distortion. The distorted NIRC2 positions of M53 stars were compared with precise astrometry of this cluster from Hubble Space Telescope observations. The resulting distortion map constructed just before the realignment is consistent with the previous solution derived using data from 2007 to 2009, indicating that the distortion has been stable to ∼0.5 mas. The distortion map changed significantly after a realignment of 4.5 mas (75%) rms, and the new distortion model for post-realignment observations have a total accuracy of ∼1.1 mas.